PENGARUH INTENSITAS ASET BIOLOGIS, UKURAN KOMITE AUDIT DAN KEAHLIAN KEUANGAN KOMITE AUDIT TERHADAP PENGUNGKAPAN ASET BIOLOGIS PADA PERUSAHAAN AGRIKULTUR YANG TERDAFTAR DI BEI - Michael Owen; Wirawan Endro Dwi Radianto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to investigate the influence of biological asset intensity, company size, audit committee size, and audit committee accounting or financial expertise on biological asset disclosure. The samples used in this study are the agriculture companies listed on the Bursa Efek Indonesia (BEI) between 2005 and 2019. The data are collected from companies annual report. This study uses quantitative method with multiple linear regression analysis. The result shows that biological asset intensity, company size, audit committee size, and audit committee accounting or financial expertise have negative influence on the biological asset disclosure. This study contributes as literature for academics and provide perspective for all parties that have interest towards biological asset disclosure in Indonesia.